Adipose Tissue‐Derived Omentin‐1 Function and Regulation. Issue 3 (18th June 2017) - Watanabe, Takuya; Watanabe‐Kominato, Kaho; Takahashi, Yui; Kojima, Miho; Watanabe, Rena
ABSTRACT: Omentin‐1, also known as intelectin‐1, is a recently identified novel adipocytokine of 313 amino acids, which is expressed in visceral (omental and epicardial) fat as well as mesothelial cells, vascular cells, airway goblet cells, small intestine, colon, ovary, and plasma. The level of omentin‐1 expression in (pre)adipocytes is decreased by glucose/insulin and stimulated by fibroblast growth factor‐21 and dexamethasone. Several lines of experimental evidence have shown that omentin‐1 plays crucial roles in the maintenance of body metabolism and insulin sensitivity, and has anti‐inflammatory, anti‐atherosclerotic, and cardiovascular protective effects via AMP‐activated protein kinase/Akt/nuclear factor‐κB/mitogen‐activated protein kinase (ERK, JNK, and p38) signaling. Clinical studies have indicated the usage of circulating omentin‐1 as a biomarker of obesity, metabolic disorders including insulin resistance, diabetes, and metabolic syndrome, and atherosclerotic cardiovascular diseases. It is also possible to use circulating omentin‐1 as a biomarker of bone metabolism, inflammatory diseases, cancers, sleep apnea syndrome, preeclampsia, and polycystic ovary syndrome. Decreased omentin‐1 levels are generally associated with these diseases. However, omentin‐1 increases to counteract the acute phase after onset of these diseases. These findings indicate that omentin‐1 may be a negative risk factor for these diseases, and also act as an acute‐phase reactant by its anti‐inflammatory and atheroprotective effects. Therapeutic strategies to restore omentin‐1 levels may be valuable for the prevention or treatment of these diseases. Weight loss, olive oil‐rich diet, aerobic training, and treatment with atorvastatin and antidiabetic drugs (metformin, pioglitazone, and exenatide) are effective means of increasing circulating omentin‐1 levels. This review provides insights into the potential use of omentin‐1 as a biomarker and therapeutic target for these diseases. © 2017 American Physiological Society. Compr Physiol 7:765‐781, 2017.